CompTIA security+ study guide - Pastore, Michael A. (Wiley, 2006)
"Take charge of your career with certification that can increase your marketability. This new edition of the top-selling Guide is what you need to prepare for CompTIA's Security+ SY0-101 exam. Developed to meet the exacting requirements of today's certification candidates and aspiring IT security professionals, this fully updated, comprehensive book features: Clear and concise information on crucial security topics; Practical examples and hands-on labs to prepare you for actual on-the-job situations; Authoritative coverage of all key exam topics including general security concepts; communication, infrastructure, operational, and organizational security; and cryptography basics"--Resource description page.